2021
DOI: 10.1101/2021.08.30.21262866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 mRNA Vaccination-Associated Myocarditis in Children Ages 12-17: A Stratified National Database Analysis

Abstract: Objectives: Establishing the rate of post-vaccination cardiac myocarditis in the 12-15 and 16-17-year-old population in the context of their COVID-19 hospitalization risk is critical for developing a vaccination recommendation framework that balances harms with benefits for this patient demographic. Design, Setting and Participants: Using the Vaccine Adverse Event Reporting System (VAERS), this retrospective epidemiological assessment reviewed reports filed between January 1, 2021, and June 18, 2021, among ado… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…34 44 47-50 53-56 and three case series compiled from publicly available websites (Public Health Agency of Canada, PHAC; UK's Medicines & Healthcare Products Regulatory Agency [Yellow Card database], UK;…”
mentioning
confidence: 99%
“…34 44 47-50 53-56 and three case series compiled from publicly available websites (Public Health Agency of Canada, PHAC; UK's Medicines & Healthcare Products Regulatory Agency [Yellow Card database], UK;…”
mentioning
confidence: 99%
“…Forty-six studies were included in this update ( Figure 1 ). Findings from 12 studies from the original review 15 were carried forward (Q1=5 2529 , Q2=2 29 30 , Q3b. 2528 3136 ).…”
Section: Resultsmentioning
confidence: 99%
“…Findings from 12 studies from the original review 15 were carried forward (Q1=5 2529 , Q2=2 29 30 , Q3b. 2528 3136 ). From the search update, we identified 34 new reports across all questions (Q1=9 3745 , Q2=5 37 41 4547 , Q3=1 48 , Q4=3 39 49 50 , Q5=21 9 5170 ); we excluded five studies that only reported on combined myo- and/or pericarditis (as we located other studies with these reported separately), 7175 eight studies that did not report on confirmed cases, 7683 and three studies 8486 that did not contribute additional data to other included studies on the same cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that new data from campaigns with several millions of vaccinated children have emerged, potential risks of rare but serious adverse reactions following vaccination for this age group can now be quantified more reliably. A study from the USA, 2 posted as a preprint on 30 August found that the risk of myocarditis within 5 days of the second dose of the vaccine is 2–6 times higher than the 120‐day risk of hospitalisation in boys 12–17 without underlying medical conditions. An article from Israel 3 published on 25 August 2021, involving almost one million vaccinated persons above 16 years of age, has concluded that vaccination was most strongly associated with an elevated risk of myocarditis (RR 3.24; 95% CI 1.55,12.44); the median age of persons with myocarditis was 25 years and 90.9% were male.…”
mentioning
confidence: 99%